Corrosion behavior of AZ91 Mg alloy with a heterogeneous structure produced by ECAP. (15th July 2021) - Yang, Zhenquan; Ma, Aibin; Xu, Bingqian; Jiang, Jinghua; Sun, Jiapeng
Highlights: The corrosion behavior of AZ91 Mg alloy with heterogenous structure was explored. The heterogenous grain structured AZ91 Mg alloy showed improved corrosion resistance. Post-ECAP aging enhanced the micro-galvanic effect and increased the corrosion rate. Coarse grain region showed higher corrosion susceptibility than fine grain region. Abstract: The microstructure of a commercial AZ91 Mg alloy was modified via equal channel angular pressing (ECAP) and subsequent aging. Immersion corrosion testing in 3.5 wt.% NaCl solution indicated that the ECAP alloy with heterogeneous grain structure had the best corrosion performance, which mainly stemmed from that the galvanic effect was weakened due to the reduced fraction and modified distribution of β phase particles. An aging treatment consisting of 60–90 h at 150 ℃ produced fine β phase precipitates which enhanced the micro-galvanic effect, such that the corrosion rates increased but were still lower than that of the as-cast alloy.